Montelukast-induced alveolar hemorrhage: report of a case - Martinez Montalvo, Carlos M. (2020)
Diffuse alveolar hemorrhage is a pathological finding, defined as a consequence of a lesion in pulmonary microcirculation which occurs with non-specific symptoms, and sometimes it may show no symptoms. Three histopathological diagnoses are to be differentiated. The most common is capillary inflammation, which is secondary to autoimmune conditions. We present the case of a patient with image studies and bronchoalveolar lavage compatible with diffuse alveolar hemorrhage, in whom autoimmune and infectious causes were ruled out. The history of the patient indicated recent use of montelukast, being this time-related with the patient’s clinical condition. The patient responded when the drug was withheld, image studies showed particular findings, and results in the Naranjo ADR scale supported the diagnosis.